Evaluation of Competency Test and Work Competency Certification Implementations at Professional Certification Institute - First Party (LSP P1) - Rosyid, Arif (Journal of Vocational and Career Education, 2020)
The challenge of vocational education is to produce competent and competitive prospective workers. Competency certification is a strategic step to improve the quality of Vocational High School graduates. For Vocational High School LSP P1 implementing the work competency certification, its function is not optimal and its independence is questionable. Vocational High School LSP P1Ã‚Â  is only 4% compared to the number of Vocational High Schools and the graduates. Evaluation for Vocational High School LSP P1 was conducted to find out how the implementation of competency tests and work competency certification. This research aims to evaluate the implementation of competency test and work competency certification at LSP P1, in terms of the component variables of Context, Input, Process, and Product. This research is a descriptive evaluative research using the CIPP evaluation model approach. The research population was Vocational High School LSP P1 assessors from 9 Vocational High Schools in Pekalongan Regency and its surroundings. The sample was the research population who served as competency test assessors at LSP P1. Data collection methods in this research were questionnaire, interview, and document study. The content validity testing was by expert judgment, while the construct validity testing was by correlation analysis. The reliability test used Alpha Cronbach. The data analysis technique was quantitative descriptive analysis. Furthermore, it was analyzed by changing the scores for the context, input, process, and product components into a T-Score and then categorized them by the Glickman Quadrant. The research results were as follows; (1) in the context component, the percentage was F + = 66% and F - = 34% meaning that the implementation of competency test in terms of context variables is categorized as effective, (2) for the input component, the percentage was F + = 61% and F - = 39%, indicating that the implementation of competency test in terms of input variable is categorized as effective, (3) for the process component, the percentage was F + = 66% and F - = 34%, meaning that the implementation of competency test in terms of process variable is categorized as effective, (4) for the product component, the percentage was F + = 59% and F - = 41%, indicating that the implementation of competency test in terms of the product variable is categorized as effective, (5) T-score analysis of the four CIPP components, namely context, input, process, and product were (+ + + +) in the criteria of the Glickman Quadrant that were included in quadrant I, meaning that evaluation of the implementation of competency tests and work competency certification at LSP P1 in terms of all CIPP components is in the very effective or excellent category.